2008
DOI: 10.1016/j.smallrumres.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between Spanish Assaf (Assaf.E) and Spanish native dairy sheep breeds

Abstract: a b s t r a c tAt present, the Assaf is the main dairy sheep in Spain. The Spanish Assaf (Assaf.E) was formed by male-mediated absorption of native Spanish sheep. Here we assess the genetic relationships among the Assaf.E and major native Spanish dairy breeds using microsatellites to contribute to the knowledge of the formation and within-population genetic variability of the breed. Blood samples from 44 unrelated Assaf.E individuals from 23 different Assaf.E flocks spread throughout 6 different Spanish provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
4
22
2
3
Order By: Relevance
“…In South African sheep breeds, the AR and H o values were significantly lower than those obtained in the BAR (Soma et al, 2012). Previous studies presented the same range of within-breed genetic variability in Italian sheep breed (Bozzi et al, 2009;Lasagna et al, 2011;Tolone et al, 2011) and in Austrian and Spanish sheep breeds (Baumung et al, 2006;Legaz et al, 2008), whereas Bhatia (2004, 2006) and Sodhi et al (2006) found lower values while investigating Indian sheep breeds. The large genetic diversity of the BAR was also demonstrated by Khaldi et al (2010) andEl Hentati et al (2012) using RAPD markers.…”
Section: Discussionmentioning
confidence: 66%
“…In South African sheep breeds, the AR and H o values were significantly lower than those obtained in the BAR (Soma et al, 2012). Previous studies presented the same range of within-breed genetic variability in Italian sheep breed (Bozzi et al, 2009;Lasagna et al, 2011;Tolone et al, 2011) and in Austrian and Spanish sheep breeds (Baumung et al, 2006;Legaz et al, 2008), whereas Bhatia (2004, 2006) and Sodhi et al (2006) found lower values while investigating Indian sheep breeds. The large genetic diversity of the BAR was also demonstrated by Khaldi et al (2010) andEl Hentati et al (2012) using RAPD markers.…”
Section: Discussionmentioning
confidence: 66%
“…The program STRUCTURE (Pritchard et al, 2000) was also used to ascertain a possible cryptic genetic structure in the analysed dataset (Álvarez et al, 2004;Legaz et al, 2008). The most likely number of clusters K (populations or breeds) present in a dataset was approached as the mode of the K distribution (Evanno et al, 2005).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The Assaf sheep breed was created in Israel by cross-breeding the East Friesian (Milchschaf) with the Awassi breed (Goot 1986). The breed was introduced in Spain mainly by the male-mediated absorption of Spanish native dairy sheep breeds mainly the Castellana, Churra, Manchega and also Latxa (Ugarte et al 2002, Legaz et al 2008. This absorption process was clarified at the genomic DNA level (Legaz et al 2008) and at the mitochondrial DNA level (Pedrosa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The breed was introduced in Spain mainly by the male-mediated absorption of Spanish native dairy sheep breeds mainly the Castellana, Churra, Manchega and also Latxa (Ugarte et al 2002, Legaz et al 2008. This absorption process was clarified at the genomic DNA level (Legaz et al 2008) and at the mitochondrial DNA level (Pedrosa et al 2007). It has also been demonstrated that today this breed can be considered as a unique compact and sufficiently homogenized population (Legaz et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation